2020
DOI: 10.3892/etm.2020.9467
|View full text |Cite
|
Sign up to set email alerts
|

Investigational drugs with dual activity against HBV and HIV (Review)

Abstract: Chronic hepatitis B (CHB) and acquired immunodeficiency syndrome (AIDS) are global public health problems that pose a significant health burden. Human immunodeficiency virus (HIV) and hepatitis B virus (HBV) coinfection is common, as these viruses have similar transmission routes, such as blood transmission, sexual transmission and mother-to-child transmission. Coinfection frequently leads to accelerated disease progression. For individuals coinfected with HIV/HBV, combination antiretroviral therapy containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 124 publications
(127 reference statements)
0
4
0
Order By: Relevance
“…Moreover, their use can induce HIV resistance in patients with no known HIV-infection. TDF is a generic, inexpensive, well-known and widely available drug that is currently used for HIV and HBV treatment and for HIV prophylaxis [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 72 ]. It has good pharmacological characteristics with long serum and intracellular half-life, few adverse effects and drug–drug interactions and is orally administered [ 110 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, their use can induce HIV resistance in patients with no known HIV-infection. TDF is a generic, inexpensive, well-known and widely available drug that is currently used for HIV and HBV treatment and for HIV prophylaxis [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 72 ]. It has good pharmacological characteristics with long serum and intracellular half-life, few adverse effects and drug–drug interactions and is orally administered [ 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…TDF and TAF are also extensively and efficaciously used as pre-exposure prophylaxis (PrEP) against HIV infection in people at risk of acquiring this infection [ 57 , 58 , 59 , 60 , 61 ]. The current first line therapies for chronic HBV infection also includes TDF and TAF, which have proven to be well-tolerated and also highly effective in preventing liver fibrosis progression [ 62 , 63 , 64 ]. Further, tenofovir has been proposed to reduce the risk of herpes simplex virus 1 and 2 (HSV-1, HSV-2) infections, although studies have shown conflicting results [ 65 , 66 , 67 , 68 ].…”
Section: Introductionmentioning
confidence: 99%
“…No cytotoxic effects were observed up to the high-tested concentration of 1000 nM. It also showed activity against HIV-2 in PBMCs (mean EC 50 ± SD = 3.5 ± 1.5) and against six HIV-1 isolates in MDMs (mean EC 50 ± SD = 2.5 ± 1.7 nM) [57]. Human PBMCs were used to evaluate the relative levels of TFV-PP produced by (10) and TFV.…”
Section: Tenofovir Prodrugsmentioning
confidence: 99%
“…No antagonistic interactions were recorded between (10) and any FDA-approved antiretroviral drug, such as NRTI. Thus, the prodrug could deliver high levels of the active metabolite and reduce toxicity [57].…”
Section: Tenofovir Prodrugsmentioning
confidence: 99%